Artificial Intelligence-Driven Predictive Analytics and Optimization Algorithms for Enhancing End-to-End Visibility and Resilience in Global Supply Chain Networks - Mohammad Faizal Ahamed (International Journal of Computer Science and Information Technology Research, 2025)
Global supply chain networks have become increasingly complex due to globalization, fluctuating demand, and unpredictable disruptions. Artificial Intelligence (AI)-driven predictive analytics and optimization algorithms offer real-time insights, risk mitigation, and enhanced resilience in supply chain operations. This paper explores AI methodologies for optimizing supply chain networks, improving visibility, and ensuring robustness against uncertainties. It includes a review of relevant literature, examines AI-based predictive models, optimization techniques, and discusses practical applications through case studies. The study highlights AI's role in enhancing supply chain decision-making, reducing costs, and fostering sustainability.